2020
DOI: 10.21037/tcr.2020.01.60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local surgery on outcomes of stage IV breast cancer

Abstract: Metastatic breast cancer (MBC), including de novo stage IV, is regarded as being incurable and the mainstay of clinical management is systemic therapy. Traditionally, locoregional surgery is performed only for local control, such as to prevent ulceration and bleeding. In recent years, however, both retrospective and prospective studies have demonstrated the prognostic efficacy of primary surgery for de novo stage IV patients. Therefore, we conducted a meta-analysis to evaluate whether surgical therapy contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…One meta-analysis of 19 retrospective studies revealed the pooled hazard ratio (HR) of local surgery vs. systemic therapy alone to be 0.65 with a 95% confidence interval (95% CI) of 0.60–0.71 (p < 0.01), indicating that overall survival was significantly improved by surgical resection of the primary lesion ( 4 ). This finding was supported by another meta-analysis of 12 retrospective studies (odds ratio, 0.65; 95% CI, 0.59–0.72) ( 5 ). A large meta-analysis of 34 retrospective studies and 3 prospective randomized studies found surgical resection to significantly reduce mortality (HR, 0.64; 95% CI, 0.60–0.68) ( 6 ).…”
Section: Surgery For the Primary Breast Cancer In Patients With ...mentioning
confidence: 52%
“…One meta-analysis of 19 retrospective studies revealed the pooled hazard ratio (HR) of local surgery vs. systemic therapy alone to be 0.65 with a 95% confidence interval (95% CI) of 0.60–0.71 (p < 0.01), indicating that overall survival was significantly improved by surgical resection of the primary lesion ( 4 ). This finding was supported by another meta-analysis of 12 retrospective studies (odds ratio, 0.65; 95% CI, 0.59–0.72) ( 5 ). A large meta-analysis of 34 retrospective studies and 3 prospective randomized studies found surgical resection to significantly reduce mortality (HR, 0.64; 95% CI, 0.60–0.68) ( 6 ).…”
Section: Surgery For the Primary Breast Cancer In Patients With ...mentioning
confidence: 52%
“…[ 13a,34 ] Several clinical trials have been initiated to test the effect of surgical removal on metastatic breast cancer. [ 35 ] The proposed nanotherapeutic strategy may be effective in managing surgery‐associated inflammation stress. [ 36 ] Moreover, given the importance of proinflammatory mediators in shaping the immunosuppressive microenvironment (e.g., neutrophils well recognized as myeloid‐derived suppressor cells) both in the primary tumor and premetastatic niche, our findings can be used to explore potential synergy with immunotherapy, which is the focus of our current research.…”
Section: Resultsmentioning
confidence: 99%
“…First, therapy choices are partly determined by the variable of interest (de novo versus metachronous MBC in uences therapy choices) and are therefore not a confounder but an intermediary variable. Second, speci cally in de novo MBC a RCT reported that local therapy of the primary tumour did not improve OS [10,11], so local therapy is not a confounder either. Likelihood ratio tests of Cox PH models were used to compare OS between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in de novo MBC the best approach regarding the primary tumour is still unclear. Many studies suggested an overall survival (OS) bene t of local treatment [7][8][9], but recent randomized studies have refuted this [10,11]. Unlike patients with de novo MBC, many patients with metachronous MBC have already received (neoadjuvant or adjuvant) systemic treatment in addition to loco-regional treatment following diagnosis of the primary tumour.…”
Section: Introductionmentioning
confidence: 99%